Advances in micro and nano-engineered materials for high-value capacitors for miniaturized electronics. (15th November 2022) - Gupta, Rajeev; Kumar, Adesh; Biswas, A.; Singh, Rajesh; Gehlot, Anita; Akram, Shaik Vaseem; Verma, Ajay Singh
Abstract: High-powered built-on nanostructures are gaining attention for implementing innovative energy storage technologies with maximum energy storage and burst power. Due to the rapid increase in energy requirements for portable and wearable electronics, the development of tiny, environmentally friendly, and lightweight energy storage systems has gained significant attention. Nanostructured components are being utilized to adapt and optimize energy storage devices such as supercapacitors and batteries. The excessive power density and advanced energy density nanocapacitor arrays have been intensively investigated for the potential generation of energy storage techniques, among other nanostructure-based energy storage devices. The authors have reviewed state-of-the-art research articles based on the recent developments, applications, and the analysis for different capacitors on distinct dielectric materials namely: Tantalum Oxide Capacitors; Interlayer Dielectric Capacitors; Voltage Tunable Perovskites, and Non-ferroelectric microwave capacitors; High Dielectric Constant Polymer Based Pastes; High Dielectric Constant Ferroelectric Polymer-Based Composites for Thin Film Flexible Capacitors and Electrochemical Double Layer Capacitors. Moreover, the overview of the status and trends of research and development in materials and processes, including nano-engineered dielectric materials, are addressed. Finally, the future directions for developing viable capacitor technologies for advanced miniature electronic devices. Highlights: Presents Micro and Nano-Engineered Materials for High-Value Capacitors for Miniaturized Electronics State-of-the-art capacitor is discussed for energy storage and embedded applications A deep fundamental understanding of the nanoparticle's orientation and nanoparticles-polymer interfacial chemistry to gain control over nanoparticles. An Overview of the state-of-the-art capacitor technologies based on different nanostructured materials.